2010
DOI: 10.1002/cbm.753
|View full text |Cite
|
Sign up to set email alerts
|

Prison health‐care wings: Psychiatry's forgotten frontier?

Abstract: Prison health-care wings operate front-line mental illness triaging and recognition functions and also provide care for complex individuals who display behavioural disturbance. Services are not equivalent to those in hospitals, nor the community, but instead reflect the needs of the prison in which they are situated. There is a recognised failure to divert at earlier points in the criminal justice pathway, which may be a consequence of national failure to fund services properly. Hospital treatment is often del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…Women who used the MHAU, regardless of their final destination, were diagnostically heterogeneous. The rate of personality disorder was much higher than that reported among men in a similar unit in more or less the same catchment area (Forrester et al, ), although Hassan et al () showed no difference in symptom severity, a study of male and female prisoners and its association with types of mental health intervention – only a tendency for those with psychosis to get a hospital transfer. Most epidemiological studies of prisoners focus exclusively on diagnosis, although there has been some previous study of need in conjunction with diagnosis, at least in the UK (Gunn et al, 1991; Maden et al, ).…”
Section: Discussionmentioning
confidence: 69%
“…Women who used the MHAU, regardless of their final destination, were diagnostically heterogeneous. The rate of personality disorder was much higher than that reported among men in a similar unit in more or less the same catchment area (Forrester et al, ), although Hassan et al () showed no difference in symptom severity, a study of male and female prisoners and its association with types of mental health intervention – only a tendency for those with psychosis to get a hospital transfer. Most epidemiological studies of prisoners focus exclusively on diagnosis, although there has been some previous study of need in conjunction with diagnosis, at least in the UK (Gunn et al, 1991; Maden et al, ).…”
Section: Discussionmentioning
confidence: 69%
“…Such lack of basic knowledge hinders clinical intervention in community corrections and other reentry efforts, because mental health problems, substance abuse, and criminal activities are well known to correlate strongly with one another (Forrester, Chiu, Dove, & Parrott, 2010; Sacks et al, 2009; Shinkfield, Graffam, & Meneilly, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Some of the MHIT functions have been described previously (Forrester, Chiu, Dove, & Parrott, 2010). The prison had an operating capacity of almost 800 and the MHIT had a caseload of around 60 patients, turning over around 20 patients every month.…”
Section: Settingmentioning
confidence: 98%